2018
DOI: 10.17159/2309-8309/2018/v17n1a7
|View full text |Cite
|
Sign up to set email alerts
|

Range of movement, power and pinch grip strength post flexor tendon repair

Abstract: Background: Flexor tendon injuries (FTI) are common hand injuries that pose a challenge to the multidisciplinary team. Despite being the most researched topic in hand literature, the optimal surgical and post-operative treatment of FTI remains unclear and results after flexor tendon repair (FTR) continue to be unpredictable. Purpose: The purpose of this study was to determine the range of movement (ROM), power and pinch grip strength post FTR and to establish factors that may affect these. Method: The study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
(50 reference statements)
0
6
0
2
Order By: Relevance
“…Another South African flexor tendon injury longitudinal observational study reported a 49.5% rate of follow-up of non-attendance. Patients who received a controlled active motion protocol achieved better results than patients who received passive motion protocols but outcomes for both protocols were markedly worse than those achieved internationally 5 . A number of factors were statistically related to these poor outcomes including a language barrier.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Another South African flexor tendon injury longitudinal observational study reported a 49.5% rate of follow-up of non-attendance. Patients who received a controlled active motion protocol achieved better results than patients who received passive motion protocols but outcomes for both protocols were markedly worse than those achieved internationally 5 . A number of factors were statistically related to these poor outcomes including a language barrier.…”
Section: Introductionmentioning
confidence: 76%
“…Therapy-related factors included the use of meaningful activity in intervention, splints that are comfortable and look acceptable, and strategies for the management of pain 16 . Local evidence suggests that the absence of a language barrier in hand rehabilitation supports compliance 5 , implying the need for use of South African languages (or appropriate alternatives) that are accessible to patients 32 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Os ensaios clínicos apresentaram pacientes com lesões tendinosas com idade que variou de 15 a 75 anos. Em geral, todos os pacientes que participaram dos estudos tiveram a zona de lesão da mão classificada, a mais prevalente no estudo de Spark et al [9] foi a zona V com (40%) dos participantes sendo acometidos pela lesão. Porém, nos estudos de Farzad et al [8] houve uma predominância maior na zona 2, entretanto, no estudo de Rigó et al [10] não teve uma relevância entre as zonas, apenas uma variação entre as zonas de I a III.…”
Section: Discussionunclassified
“…More, Much more!") until grip strength increased to the top, then said, "enough stop" grip strength was recorded, rounded to the nearest pound and the sign has been returned to zero [10] (Figure 4).…”
Section: Measurementsmentioning
confidence: 99%